IMPLEMENTASI UNDANG-UNDANG NOMOR 2 TAHUN 2014 TERHADAP KEWENANGAN DALAM PEMBINAAN DAN PENGAWASAN NOTARIS GUNA PENINGKATAN PELAKSANAAN JABATAN NOTARIS DI INDONESIA (STUDI KASUS MAJELIS PENGAWAS DAERAH JAKARTA BARAT YANG BERADA DI JAKARTA BARAT) - Nickyta Firmaniar; Gunawan Djajaputra (Faculty of Law - Tarumanagara University, 2020)
.A. Notary holds an important role in creating legal certainly and protection for the community by issuing authentic deed which is made before him and serves as a perfect proof. With the duties and responsibilities held by Notaries are under supervision which is carried out by the authorities of the Notary is that the Notary fulfill the requirements to safeguard the public’s interests when they are carrying out their duties. The existence of Law Number 2 Year 2014 concerning the Amendment to Law Position should become a law-abiding rule for all Notaries in Indonesia which explicitly provisioned regarding the guidance, supervision, prohibition, and sanctions. Further, its implementing regulations also regulate comprehensively regarding the responsibilities and obligations of the Notary Supervisory Board in conducting its supervising duty.One of the legal issues in this study is regarding the regulation of supervisory and coaching authority under Law Number 2 Year 2014 concerning Amendment to Law Number 30 Year 2004 concerning Notary Position when a Notary Commits a violation in his role as in Notary Position as well as in Notary organizations.The research method used in this paper is Empirical Juridical Method by studying primary, secondary, and tertiary data that is analyzed qualitatively. To strengthen this research, interviews were held with relevant parties at the research location.In carrying out this duty, a Notary must comply and act in accordance with Law Number 2 Year 14 concerning Amendment to Law Number 30 Year 2004 concerning Notary Position, Notary Code of Ethics, Civil Code of Indonesia, Criminal Code of Indonesia, and other related laws and regulations. Therefore, a Notary will perform well and in accordance with the rules, and also will be avoided from violations that may be a problem for Notary in the future.